1959
DOI: 10.1139/v59-202
|View full text |Cite
|
Sign up to set email alerts
|

The Thermodynamic Properties of the System Cellulose – Water Vapor

Abstract: The heats of wetting by water of cotton cellulose containing various amounts of adsorbed and desorbed water were measured. These measurements together with those of the water vapor sorption isotherm were used to calculate the integral and differential enthalpies, free energies, and entropies of adsorption. Irreversible effects were avoided by vacuum-drying all samples a t room temperature. The dilfercntial enthalpy values suggest hydrogen bonding. The differential entropies are explained in terms of changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1964
1964
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…Rhim and Lee [16] reported that the maximum net isosteric heats of adsorption for vegetable parchment (VP) paper, Kraft paper, and solid-bleached-sulfite (SBS) paperboard were 18.51, 27.39 and 26.80 kJ/mol, respectively, at lower moisture content. The maximum net isosteric heat of water vapor adsorption on cotton cellulose was found at about 19 kJ/mol, at low moisture content [44].…”
Section: Water Vapor Adsorption Equilibria and Isosteric Heatsmentioning
confidence: 92%
“…Rhim and Lee [16] reported that the maximum net isosteric heats of adsorption for vegetable parchment (VP) paper, Kraft paper, and solid-bleached-sulfite (SBS) paperboard were 18.51, 27.39 and 26.80 kJ/mol, respectively, at lower moisture content. The maximum net isosteric heat of water vapor adsorption on cotton cellulose was found at about 19 kJ/mol, at low moisture content [44].…”
Section: Water Vapor Adsorption Equilibria and Isosteric Heatsmentioning
confidence: 92%
“…[42][43][44] Water adsorption into the plant cell wall is accompanied by a release of heat into the environment due to a reduction in energy of the water molecules as they are confined within the cell wall microcapillaries. 17,45 The heat energy released is in addition to the latent heat given off when water vapor condenses to a liquid. Measurement of this ''heat of wetting'' can use calorimetric methods (integral heat of wetting), or can be estimated by application of the Clausius-Clapeyron equation (differential heat of wetting).…”
Section: Introductionmentioning
confidence: 99%
“…The following assumptions were made in the calculations: (a) the 20 oat crowns used in the analysis were cylindrical and of uniform size (height ϭ 20 mm, diameter ϭ 6 mm); (b) all the cells in the crown were spheres with a diameter of 0.01 mm; (c) the 3.6 mg of water freezing in the 20 oat crowns had a volume of 3,600 mm 3 ; and (d) a liquid water mono-layer is 3 Å thick. (Morrison and Dzieciuch, 1959). Olien (1974) reported that a liquid water layer 6 monomers thick would result in strong adhesions, and that no adhesions were present with a liquid water layer 15 monomers thick.…”
Section: Co 2 Effects On Thermal Activitymentioning
confidence: 99%